2022
DOI: 10.1093/ptj/pzac091
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Centered Goals After Lumbar Spine Surgery: A Secondary Analysis of Cognitive-Behavioral–Based Physical Therapy Outcomes From a Randomized Controlled Trial

Abstract: Objective The purpose of this study was to examine the association between goal attainment and patient-reported outcomes in patients who engaged in a 6-session, telephone-based, cognitive-behavioral-based physical therapy (CBPT) intervention after spine surgery. Methods In this secondary analysis of a randomized trial, data from 112 participants (mean age = 63.3 [SD = 11.2] years; 57 [51%] women) who attended at least 2 CBPT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“… No differences were found among the groups regarding lumbar ROM. Coronado et al ( 54 ) SART II 112 Examine the association between goal attainment and patient-reported outcomes in patients who engaged in a 6-session, telephone-based, CBPT intervention after spine surgery. 12 months GAS; ODI; 12-item short-form health survey; PROM information system; pain numeric rating scale.…”
Section: Lumbar Spinementioning
confidence: 99%
See 2 more Smart Citations
“… No differences were found among the groups regarding lumbar ROM. Coronado et al ( 54 ) SART II 112 Examine the association between goal attainment and patient-reported outcomes in patients who engaged in a 6-session, telephone-based, CBPT intervention after spine surgery. 12 months GAS; ODI; 12-item short-form health survey; PROM information system; pain numeric rating scale.…”
Section: Lumbar Spinementioning
confidence: 99%
“…Patients with these degenerative pathologies develop high levels of functional limitation, fear of movement and pain catastrophizing ( 5 , 15 , 45 ). In that way, studies have shown the effectiveness and importance of using exercise rehabilitation protocols combined with cognitive-behavioral therapy and patient goal attainment-based therapy, showing significant improvements in disability, back and leg pain, fear avoidance behavior, mental health and quality of life ( 1 , 2 , 5 , 13 , 15 , 45 , 54 ).…”
Section: Lumbar Spinementioning
confidence: 99%
See 1 more Smart Citation